2020
DOI: 10.3390/f11121322
|View full text |Cite
|
Sign up to set email alerts
|

Forest Cover Mapping Based on a Combination of Aerial Images and Sentinel-2 Satellite Data Compared to National Forest Inventory Data

Abstract: Research Highlights: This study developed the first remote sensing-based forest cover map of Baden-Württemberg, Germany, in a very high level of detail. Background and Objectives: As available global or pan-European forest maps have a low level of detail and the forest definition is not considered, administrative data are often oversimplified or out of date. Consequently, there is an important need for spatio-temporally explicit forest maps. The main objective of the present study was to generate a forest cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…In the field of forest remote sensing, aerial imagery is less frequently used than satellite imagery, especially when it comes to forest type classification tasks [Holzwarth et al, 2020]. This may be driven by the low number of spectral bands (red, green, blue, and near-infrared (RGB+NIR)), which is considered to be a limitation in remote sensing applications [Fassnacht et al, 2016;Ganz et al, 2020]. On the other hand, many studies have shown the strengths of multi-spectral satellite imagery for forest classification tasks [Pasquarella et al, 2018;Grabska et al, 2019;Immitzer et al, 2019;Ottosen et al, 2020;Hemmerling et al, 2021;Kollert et al, 2021;Waser et al, 2021;Welle et al, 2022].…”
Section: State Of Researchmentioning
confidence: 99%
“…In the field of forest remote sensing, aerial imagery is less frequently used than satellite imagery, especially when it comes to forest type classification tasks [Holzwarth et al, 2020]. This may be driven by the low number of spectral bands (red, green, blue, and near-infrared (RGB+NIR)), which is considered to be a limitation in remote sensing applications [Fassnacht et al, 2016;Ganz et al, 2020]. On the other hand, many studies have shown the strengths of multi-spectral satellite imagery for forest classification tasks [Pasquarella et al, 2018;Grabska et al, 2019;Immitzer et al, 2019;Ottosen et al, 2020;Hemmerling et al, 2021;Kollert et al, 2021;Waser et al, 2021;Welle et al, 2022].…”
Section: State Of Researchmentioning
confidence: 99%
“…However, the production of up-to-date information in sufficient spatial detail for operative forest management and monitoring at forest district level still does not entirely satisfy data needs [1,5,11]. As very high-resolution (VHR) satellite imagery is currently only provided by commercial companies, or can only be accessed through open data programs for scientific use (i.e., the European Space Agency Third Party Missions [12]), aerial imagery remains a crucial dataset in multiple operational forestry applications on a local scale [13][14][15]. Indeed, VHR imagery provided in at least yearly cycles would be necessary to provide the capability to monitor changes and disturbances (i.e., wind fall), whereas intra-annual data in sufficient detail would be necessary for capturing dynamic changes caused by biotic and abiotic drivers (i.e., insect calamities, drought effects) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The paper regarding large juniper forests also introduces the concept of carbon sequestration, which is particularly important to our environment today [3]. The final three papers deal with higher spatial resolution remotely sensed imagery [4][5][6]. The paper by Ganz et al [4] demonstrates the benefits of having a detailed forest map of a German forest created from high spatial resolution imagery.…”
mentioning
confidence: 99%
“…The final three papers deal with higher spatial resolution remotely sensed imagery [4][5][6]. The paper by Ganz et al [4] demonstrates the benefits of having a detailed forest map of a German forest created from high spatial resolution imagery. They then introduce the concept of comparing or relating what can be determined on the detailed map created from the remotely sensed imagery with their forest inventory data collected on the ground.…”
mentioning
confidence: 99%